Abnormal processing of interpersonal cues during an aggressive encounter in women with borderline personality disorder: neural and behavioral findings - Bertsch, Katja; Buades-Rotger, Macià; Krauch, Marlene; Ueltzhöffer, Kai; Kleindienst, Nikolaus; Herpertz, Sabine; Krämer, Ulrike M. (Journal of psychopathology and clinical science, 2022)
Inappropriate aggression is a prominent and clinically relevant interpersonal dysfunction of individuals with borderline personality disorder (BPD). Previous studies have shown that individuals with BPD interpret interpersonal signals in a hostile manner, but it is uncertain how this negativity bias impacts decision-making during aggressive encounters. In the present neuroimaging study, 48 medication-free women with BPD and 28 age- and intelligence-matched women played the Social Threat Aggression Paradigm (STAP), a competitive reaction time task in which the winner delivers an aversive sound blast to the loser. Crucially, in the STAP the alleged opponent displays either an angry or neutral facial expression at the beginning of each trial and selects increasingly loud blasts in order to provoke participants. Relative to healthy controls, women with BPD differentiated less between angry and neutral facial expressions, both in terms of aggressive behavior and of activity in medial prefrontal cortex, amygdala, and temporal pole. On the one hand, and contrary to our hypotheses, neural and behavioral responses to angry faces were reduced in women with BPD compared to healthy women. On the other hand, provocation heightened subsequent amygdala responses to neutral faces in BPD, and this was in turn associated with aggressive behavior, supporting a default negativity bias in BPD. The neurocognitive processes by which these alterations might guide aggressive behavior irrespective of interpersonal cues are presented and discussed.